International Responsibility for Environmental Damage According to the Rules of International Humanitarian Law - Bendaoud, Soufi (Journal of Legal Studies and Researches, 2023)
The protection of the environment will not emerge in a visible and effective manner except at the stage of the outbreak of armed conflicts, as the rules of the law of armed conflicts, or as it is known as international humanitarian law, must intervene in order to provide this protection through the various convention texts, which entail international responsibility on the party to the conflict that violates its provisions.